Islam Is a Foreign Country: American Muslims and the Global Crisis of Authority - Zareena Grewal (NYU Press, 2013)
Islam Is a Foreign Country intervenes not only in the debates in my scholarly fields but in the debates that are the object of this study, debates about Islamic orthodoxy and authenticity, debates about the meaning of American citizenship in a global age. I could not divorce my emotional and ethical investments in these debates any more than I could erase those of the subjects; it is precisely these emotional and political investments and our shared experiences of displacement that give this bookâ€™s debatesâ€”both the arguments I develop and those I documentâ€”their urgency. I must admit I worry about the different eyes roaming these pages for recognition, from different traditions, with different sets of expectations and, maybe, different kinds of disappointment. After all, my own claim to authority, to integrity and competence, both intellectual and cultural, is precariously balanced on these unsteady pages.53 Over the course of my research, I had to reconcile the intrinsic tensions between the different intellectual traditions I navigate, the ways in which anthropology necessarily disciplines and secularizes my analyses, ways in which I may not always be conscious. As Said notes, geographical â€œdislocation, secular discovery, and the painstaking recovery of implicit or internalized histories . . . stamp the ethnographic quest with the mark of a secular energy that is unmistakably frank.â€54 While for Said these qualities are a mark of anthropologyâ€™s worldliness, my Muslim friends and family, in their own words, identify them as intellectual limits, limits they have been warning me to anticipate since I first started out on the path of becoming a scholar. As a way of sensitizing myself to these tensions and limits, I became the student of a Ghanaian scholar and Islamic jurist, a shaykh,throughout my first few years of graduate school. Although he also holds a PhD in Islamic studies from the University of Michigan in addition to his religious credentials, he often urged me to balance my secular education as he bemoaned the fact that so many Muslim academics know more about Western philosophy than they do about their own intellectual tradition. Eager to maintain my intellectual footing in both canons, I struggled to supplement my university course packs with the reading required by my â€œotherâ€ education, but it remained hopelessly imbalanced, always more â€œhighâ€ theory than Islamic legal theory. After a long week of seminars and heavy reading loads, on Saturday afternoons I would drive out to an old, quiet Detroit neighborhood, where my shaykh had converted an old blue house neighboring his own into a modest, free counseling service center for Muslim families. Here, the other students and I would pile into a tiny, dusty room and crowd around a wobbly table for our halaqa, an Islamic study circle. For hours we would go over an Arabic text on Islamic legal theory at a painfully slow pace due to our difficulties with the classical Arabic. Occasionally, the class would be interrupted by one of the shaykhâ€™s small children hunting his deep pockets for a lollipop or by a new convert with a quick question or by a troubled, worn-out couple needing an argument mediated. Although we took our studies seriously, the study circle also became a springboard for innumerable tangential discussions. The shaykh welcomed these, made that dusty room a safe place to make any criticism or ask any question. This is where I would voice my frustrations with the racism, classism, sexism, and political impotence that permeate the Muslim communities that I work in, both in the US and in the Middle East.